Early Dorsal Midbrain Syndrome Mimicking an Adie's Tonic Pupil - Han, Sang Won (Korean Neurological Association, 2010)
BACKGROUND: While tonic pupils have been attributed to various diseases, including syphilis, herpes zoster, orbital trauma, temporal arteritis, endometriosis, and paraneoplastic syndromes, obstructive hydrocephalus has not been implicated. CASE REPORT: A 36-year-old woman visited a neurology department with a 7-day history of throbbing headache and blurred vision in both eyes. She had early dorsal midbrain syndrome mimicking an Adie's tonic pupil, and cholinergic supersensitivity was demonstrated using topical 0.125% pilocarpine. Brain MRI revealed obstructive hydrocephalus at the level of the aqueduct of Sylvius, and her symptoms resolved 4 days after surgery. CONCLUSIONS: We report a patient with early dorsal midbrain syndrome that was initially believed to represent a tonic pupil on the basis of pharmacologic testing. The findings in our patient suggested that early dorsal midbrain syndrome mimicking an Adie's tonic pupil can be caused by obstructive hydrocephalus compressing the Edinger-Westphal nucleus.